Procedure to optimize the solid angle for the colimation of the nai detector used to measure the flow rate in pipelines (Brazilian Journal of Radiation Sciences (BJRS), 2021)
The use of radiotracers of product flow ducts from the oil and gas industry allows checking of installed flow meters and knowledge of the flow profile within the duct. The time transient method is older for the flow media and gauging of the flowmeters and lower permanence of the radioactive magazine at two different points. For the oil and gas industry, it is important that there is an average rate of 0.7%, so that this value is reached by a level of necessary care. One of the points is a correct detector / duct geometry at the two measurement points because the quality of the contents depends on the passage across a straight section of the radioactive duct. The present work has the purpose of analyzing the collimation effect of the detector signal during radiotracer during flow in a steel duct using  Au198 as the radiotracer. The analysis was carried out using computer simulation using the computational code Microshield, simulating the entire face detector / shielding / collimation system of the NaI detector 2x2" and the fluid being used in conjunction with the system Glycerol in regime of turbulent flow. The study is found in the same way as the radio of the detector in the same distance of the radio reserve from the radio in the entrance to the standard of the ANP.